Energy consumption optimization for self‐powered IoT networks with non‐orthogonal multiple access. (9th September 2019) - Li, Xi; Luo, Changqing; Ji, Hong; Zhuang, Yuandong; Zhang, Heli; Leung, Victor C.M.
Summary: Energy harvesting (EH) has been considered as one of the promising technologies to power Internet of Things (IoT) devices in self‐powered IoT networks. By adopting a typical harvest‐then‐transmit mode, IoT devices with the EH technology first harvest energy by using wireless power transfer (WPT) and then carry out wireless information transmission (WIT), which leads to the coordination between WPT and WIT. In this paper, we consider optimizing energy consumption of periodical data collection in a self‐powered IoT network with non‐orthogonal multiple access (NOMA). Particularly, we take into account time allocation for the WPT and WIT stages, node deployment, and constraints for data transmission. Moreover, to thoroughly explore the impact of different multiple access methods, we theoretically analyse and compare the performance achieved by employing NOMA, frequency division multiple access (FDMA), and time division multiple access (TDMA) in the considered IoT network. To validate the performance of the proposed method, we conduct extensive simulations and show that the NOMA outperforms the FDMA and TDMA in terms of energy consumption and transmission power. Abstract : The energy consumption is optimized for periodical data collection in a self‐powered IoT network with NOMA. We take into account time allocation for the wireless power transfer and wireless information transmission stages, node deployment, and constraints for data transmission in power and data amount. Moreover, to thoroughly study the impact of different multiple access methods, we analyse and compare the performance achieved by employing NOMA, FDMA and TDMA in the considered IoT network from both theoretical discussion and simulations.